Fast exocytosis with few Ca(2+) channels in insulin-secreting mouse pancreatic B cells. - Barg, S; Ma, X; Eliasson, L; Galvanovskis, J; Göpel, S; Obermüller, S; Platzer, J; Renström, E; Trus, M; Atlas, D; Striessnig, J; Rorsman, P (2001)
The association of L-type Ca(2+) channels to the secretory granules and its functional significance to secretion was investigated in mouse pancreatic B cells. Nonstationary fluctuation analysis showed that the B cell is equipped with <500 alpha1(C) L-type Ca(2+) channels, corresponding to a Ca(2+) channel density of 0.9 channels per microm(2). Analysis of the kinetics of exocytosis during voltage-clamp depolarizations revealed an early component that reached a peak rate of 1.1 pFs(-1) (approximately 650 granules/s) 25 ms after onset of the pulse and is completed within approximately 100 ms. This component represents a subset of approximately 60 granules situated in the immediate vicinity of the L-type Ca(2+) channels, corresponding to approximately 10% of the readily releasable pool of granules. Experiments involving photorelease of caged Ca(2+) revealed that the rate of exocytosis was half-maximal at a cytoplasmic Ca(2+) concentration of 17 microM, and concentrations >25 microM are required to attain the rate of exocytosis observed during voltage-clamp depolarizations. The rapid component of exocytosis was not affected by inclusion of millimolar concentrations of the Ca(2+) buffer EGTA but abolished by addition of exogenous L(C753-893), the 140 amino acids of the cytoplasmic loop connecting the 2(nd) and 3(rd) transmembrane region of the alpha1(C) L-type Ca(2+) channel, which has been proposed to tether the Ca(2+) channels to the secretory granules. In keeping with the idea that secretion is determined by Ca(2+) influx through individual Ca(2+) channels, exocytosis triggered by brief (15 ms) depolarizations was enhanced 2.5-fold by the Ca(2+) channel agonist BayK8644 and 3.5-fold by elevating extracellular Ca(2+) from 2.6 to 10 mM. Recordings of single Ca(2+) channel activity revealed that patches predominantly contained no channels or many active channels. We propose that several Ca(2+) channels associate with a single granule thus forming a functional unit. This arrangement is important in a cell with few Ca(2+) channels as it ensures maximum usage of the Ca(2+) entering the cell while minimizing the influence of stochastic variations of the Ca(2+) channel activity.